Sulfamethoxazole-induced crystal nephropathy: characterization and prognosis in a case series - Ruben Azencot; Camille Saint-Jacques; Jean-Philippe Haymann; Vincent Frochot; Michel Daudon; Emmanuel Letavernier (Scientific Reports, 2024)
Abstract Cotrimoxazole (Trimethoprim/Sulfamethoxazole-SMX) is frequently used in critically ill and immunocompromised patients. SMX is converted to N-acetyl-sulfamethoxazole (NASM) and excreted by the kidneys. NASM may form crystals in urine, especially in acid urine, that may induce a crystalline nephropathy. However, the imputability of crystals in acute kidney injury (AKI) has not been proven. We aimed to assess whether NASM crystals may promote AKI and to investigate risk factors associated with NASM crystalline nephropathy. Patients from Ile-de-France, France who developed AKI under SMX treatment introduced during hospitalization and had a crystalluria positive for NASM crystals were selected. Patients with excessive preanalytical delay for crystalluria or missing data regarding SMX treatment were excluded. We used the Naranjo score to assess the causal relationship between SMX and the development of AKI in patients with positive NASM crystalluria. Fourteen patients were included. SMX was the probable cause of AKI for 11 patients and a possible cause for 3 patients according to Naranjo score. Patients were exposed to high doses of SMX (but within recommended ranges), and most of them had a preexisting chronic kidney disease and were hypoalbuminemic. Urine pH was mildly acid (median 5.9). AKI occured more rapidly than expected after introduction of SMX (median 4 days) and recovered rapidly after drug discontinuation in most, but not all, cases. SMX is a probable cause of crystalline nephropathy. Monitoring of crystalluria in patients exposed to SMX may be of interest to prevent the development of crystalline nephropathy. Approval number of the study: BPD-2018-DIAG-008.